2004
DOI: 10.1002/ejoc.200400071
|View full text |Cite
|
Sign up to set email alerts
|

The (Schiff base)vanadium(V) Complex Catalyzed Oxidation of Bromide − A New Method for the in situ Generation of Bromine and Its Application in the Synthesis of Functionalized Cyclic Ethers

Abstract: (Schiff base)vanadium(V) complexes 5 with tridentate imine auxiliaries served as catalysts for the oxidation of Br − with tert-butyl hydroperoxide (TBHP) in nonaqueous solvents. This reaction has been applied for the conversion of substituted 4-penten-1-ols into 5-exo-bromo-cyclized products, including a diastereomerically pure heterocyclic precursor used in a synthesis of the all-trans-configured 2,3,4,5-substituted tetrahydrofuran 2-epi-magnosalicin. Treatment of ω-substituted bis(homoallylic) alcohols with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(19 citation statements)
references
References 105 publications
1
17
0
1
Order By: Relevance
“…Therefore, mononuclear C 3 -vanadium(V) amine triphenolate complexes appear to be good structural and functional models of VHalPOs, effectively catalysing the oxidation with hydrogen peroxide of thioethers and bromide ions. A synthetically interesting application of a bromination reaction starting from bromide ions was recently reported by Hartung and co-workers [79]. They reported that a series of Schiff base containing vanadium derivatives are good catalysts in the synthesis of functionalized cyclic ethers, see Scheme 16.…”
Section: Bromination Reactionsmentioning
confidence: 98%
“…Therefore, mononuclear C 3 -vanadium(V) amine triphenolate complexes appear to be good structural and functional models of VHalPOs, effectively catalysing the oxidation with hydrogen peroxide of thioethers and bromide ions. A synthetically interesting application of a bromination reaction starting from bromide ions was recently reported by Hartung and co-workers [79]. They reported that a series of Schiff base containing vanadium derivatives are good catalysts in the synthesis of functionalized cyclic ethers, see Scheme 16.…”
Section: Bromination Reactionsmentioning
confidence: 98%
“…[48] In another study, vanadium(V)-Schiff base complexes 11 served as catalysts for the oxidative bromination of substituted 4-penten-1-ol (12) into b-brominated cyclic ethers 13 a and 13 b in the presence of pyridinium hydrobromide and tBuOOH (Scheme 3). [49] Immobilizing the Schiff base enabled recovery of the catalyst. Two variations of this principal have been used.…”
Section: Vanadium and Molybdenum Complexes As Functional Mimics Of Vamentioning
confidence: 99%
“…As a consequence and having in mind the in situ formation of α-aminohydroperoxide moieties from flavine-derived cyclophanes and hydrogen peroxide in the stereoselective sulphoxidations, 21 our strategy was turned to the combination of hydrogen peroxide, isoquinolines 7 and (R)-menthyl chloroformate 8 and metal compounds as additives (Scheme 3). Since VO(OiPr) 3 had turned out to be very useful in oxygen transfer reactions from hydrogen peroxide, [32][33][34] this compound was applied in the in situ procedure according to Scheme 3 giving rise to an enantioselective formation of the sulphoxides 2. The effect of several parameters on the enantioselectivity was screened (see table in supporting information).…”
Section: Scheme 2 Formation Of Chiral Isoquinoline-derived Peroxidesmentioning
confidence: 99%